Palmitoylethanolamide and Polydatin combination reduces inflammation and oxidative stress in vascular injury. (September 2017) - Gugliandolo, Enrico; Fusco, Roberta; Biundo, Flavia; D'Amico, Ramona; Benedetto, Filippo; Di Paola, Rosanna; Cuzzocrea, Salvatore
Graphical abstract: Abstract: Acute and chronic inflammation responses are important risk factors for vascular remodeling processes such as in atherosclerosis, arteriosclerosis and restenosis. Inflammation and oxidative stress in the intimal region after vascular damage are a key event in the development of neointimal hyperplasia. In this study, we used this model of vascular damage, which involves the complete ligature of the left carotid artery for 14 days, to observe the role of N-palmitoylethanolamine in combination with Polydatin at the dose of 30 mg/kg, on regulation of inflammatory process, and oxidative stress. Palmitoylethanolamide (PEA), an endogenous fatty acid amide belonging to the N-acylethanolamine family, has anti-inflammatory and neuroprotective effects. However, PEA lacks direct capacity to prevent formation of free radicals. Polydatin (PLD) that is a natural precursor of resveratrol has antioxidant activity. Thus, the combination of PEA and PLD could have beneficial effects on inflammatory process and oxidative stress. This model shows that 14 days after carotid artery ligation there is a significant structural change within the vessel, and that there is an important involvement of the inflammatory pathway in the progression of this disease. In this study we demonstrated that PEA/PLD combination treatment reduces vessel damage, adhesion molecules expression such as intercellular adhesion molecules-1(ICAM-1) and vascular cell adhesion molecules-1(V-CAM), proinflammatory cytokines production (Tumor Necrosis Factor alpha (TNF-α) and Interleukin 1 beta (IL-1β), the inducible nitric oxide synthase (iNOS) and Poly (ADP-ribose) polymerase (PAR), formation, Nuclear factor kappa-B expression and apoptosis (BAX, Fas-Ligand) activation. Our results clearly demonstrated that treatment with PEA/PLD 30 mg/Kg is able to reduce vascular damage and attenuates the inflammatory process.